The art-historical interests of Francesco Saverio Quadrio (ACME, 2024)
The article addresses the historical-artistic interests of the scholar and historian Francesco Saverio Quadrio (Ponte in Valtellina 1695-Milan 1756). Quadrio is known especially for his research history of the poetry and his studies on his native land, the Valtellina. In his books he has collected and combined various information on artists and works of art. Not all the information he has collected is reliable, but his studies were nevertheless one of the sources for updating important volumes for their great international circulation, such as the studies of Johann Caspar Füssli or the famous Dictionary of Painters Pilkington. An effort has been made to understand Quadrio’s working method, investigating the origin of his hypotheses, but also the effects of these in successive historiography.
Keywords: Francesco Saverio Quadrio; Valtellina; artistic literature; painting in Valtellina and Alto Lario between the 15th and 18th centuries; Cesare Ligari; Pietro Ligari